Analisis Kepatuhan Pajak Badan Menggunakan Pendekatan Laporan Keuangan - , IKSA AYU MAHARANI, Dr. Eko Suwardi, M.Sc., CMA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this research is to described the tax compliance of the firms by analyzing the financial statement. The profitability ratio of the financial statement will be calculated. It fits with the risk of offshore profit shifting. Samples of this research are 58 companies listed as manufacturing companies in Indonesia Stock Exchange from 2009 until 2012. Profitability ratio used in this research are Gross Profit Margin, Net Profit Margin, Berry, EBIT, and ROA. The results showed that almost of the firm have the high risk to not comply with the tax rule. The compliance to the tax have the fluctuative trends from 2009 to 2012.